Estrategias de comunicación digital para el posicionamiento de la imagen corporativa del Gobierno Autónomo Descentralizado Parroquial Rural Bilován, cantón San Miguel, provincia Bolívar, año 2022 - Castro Morales, Debora Elizabeth (2022)
The research project proposes to develop digital communication strategies for the positioning of the corporate image of the Autonomous Decentralized Rural Parish Government of Bilován, to provide solutions regarding the communication problems that arise in the institution, the methodology applied in the development of The research is mixed quantitative-qualitative, for which surveys were carried out with the external public and interviews with the internal public, where the needs of the institution were known, such as: not having a professional in the Communication area, the poor dissemination of information regarding the works and procedures carried out by the GAD during its administration, which has caused disinformation and disinterest in the citizenry, thus affecting the position of the institution, with the interpretation of results, the strategies and tactics that were applied according to the needs of the institution and the c citizenship